HUBUNGAN ANTARA BURNOUT TERHADAP ACADEMIC PROCRASTINATION (Pada Mahasiswa Fakultas Keguruan Ilmu Pendidikan Universitas PGRI Banyuwangi) - Jimmy Andhika Akbar; Raup Padillah; Fajar Wahyu Prasetyo (Program Studi Bimbingan dan Konseling, 2022)
Education is an essential thing and is a method used to obtain learning from various disciplines. Education also cannot be separated from human life in the family, community, and nation. Education's level of success can also determine a nation's progress. Burnout and Academic Procrastination are widespread phenomena in the academic field where students delay academic tasks such as studying for exam preparation, completing assignments, and performing educational administration. This study aims to analyze the effect of Burnout on academic procrastination in FKIP students at PGRI Banyuwangi University. In this study, data collection was obtained using an online questionnaire. The sample in the survey used 5th-semester students of FKIP Universitas PGRI Banyuwangi, with as many as 101 respondents. The results of this study indicate that Burnout has a significant effect on academic procrastination, with a 70% Rsquere on the value of simple linear regression. This study suggests that improved time management for FKIP students and teaching staff should better understand the student's current condition..